Cannabis-Based Oral Formulations for Medical Purposes: Preparation, Quality and Stability - Francesca Baratta; Marco Simiele; Irene Pignata; Lorenzo Ravetto Enri; Antonio D'Avolio; Riccardo Torta; Anna De Luca; Massimo Collino; Paola Brusa (MDPI AG, 2021)
Current legislation in Italy provides that medical Cannabis may be administered orally or by inhalation. One of the fundamental criteria for the administration of oral formulations is that they deliver a known consistent quantity of the active ingredients to ensure uniform therapies leading to the optimisation of the risks/benefits. In 2018, our group developed an improved Cannabis oil extraction technique. The objective of the present work was to carry out a stability study for the oil extracts obtained by this method. Furthermore, in order to facilitate the consumption of the prescribed medical Cannabis therapy by patients, a standard procedure was defined for the preparation of a single-dose preparation for oral use (hard capsules) containing the oil extract; thereafter, the quality and stability were evaluated. The hard capsules loaded with the oil extract were analysed and found to be uniform in content. The encapsulation process did not alter the quantity of the active molecule present in the oil. The stability tests yielded excellent results. Since the capsule dosage form is easily transported and administered, has pleasant organoleptic properties and is stable at room temperature for extended periods of time, this would facilitate the adherence to therapy by patients in treatment.